2015
DOI: 10.1002/oby.21079
|View full text |Cite
|
Sign up to set email alerts
|

Importance of substantial weight loss for altering gene expression during cardiovascular lifestyle modification

Abstract: Objective: To examine relationships between weight loss through changes in lifestyle and peripheral blood gene expression profiles. Methods: A prospective nonrandomized trial was conducted over 1 year in participants undergoing intensive lifestyle modification to reverse or stabilize progression of coronary artery disease. Cardiovascular risk factors, inflammatory biomarkers, and gene expression as a function of weight loss were assessed in 89 lifestyle participants and 71 retrospectively matched controls unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Loss of adipose tissue mediated by dietary changes, exercise, liposuction, or bariatric surgery (discussed in the section on Bariatric Surgery) is accompanied by decreased markers of adipose tissue and systemic inflammation (537,538). Weight loss achieved through calorie restriction and/or exercise resulted in decreased systemic IL-6, CRP, TNFα, MCP-1, soluble intercellular adhesion molecule-1 (ICAM-1), and vascular cell adhesion molecule-1 (VCAM-1) (273,(539)(540)(541)(542). Fat loss by liposuction yielded similar changes in systemic inflammatory markers in one study (543), but did not improve plasma cytokine levels in another (407).…”
Section: Lifestyle Modifications: Including Exercisementioning
confidence: 99%
“…Loss of adipose tissue mediated by dietary changes, exercise, liposuction, or bariatric surgery (discussed in the section on Bariatric Surgery) is accompanied by decreased markers of adipose tissue and systemic inflammation (537,538). Weight loss achieved through calorie restriction and/or exercise resulted in decreased systemic IL-6, CRP, TNFα, MCP-1, soluble intercellular adhesion molecule-1 (ICAM-1), and vascular cell adhesion molecule-1 (VCAM-1) (273,(539)(540)(541)(542). Fat loss by liposuction yielded similar changes in systemic inflammatory markers in one study (543), but did not improve plasma cytokine levels in another (407).…”
Section: Lifestyle Modifications: Including Exercisementioning
confidence: 99%
“…Studies show that CR does not need to be prolonged for a long time to be effective, with the advantage that shortterm CR is easier to include in clinical practice. In this context, a genomic analysis revealed that the results obtained from short-and long-term CR were similar [65]. It is one of the most common and cost-effective interventions used to induce body weight reduction and control CVD risk factors.…”
Section: Caloric Restrictionmentioning
confidence: 82%
“…It is important to note that the induction of negative energy balance is mandatory for achieving the metabolic benefits of weight loss. Benefits on CV risk factors by reducing the daily caloric intake have been widely described in obese subjects [7,[65][66][67]. CR reduces body weight, waist circumferences (visceral fat), serum lipids, insulin level and improves insulin sensitivity.…”
Section: Caloric Restrictionmentioning
confidence: 99%
“…However, gene set enrichment analysis suggested that the intervention might have affected molecular pathways controlling endothelial cell growth. In this respect, Ellsworth et al [33] have recently detected The data were analysed with the Wilcoxon test within each subgroup (the asterisks represent significant changes from baseline: * p \ 0.05; ** p \ 0.01; *** p \ 0.001; **** p \ 0.0001) and with the Mann-Whitney test between the subgroups (DPI B -10 % vs. DPI [ -10 %).…”
Section: Discussionmentioning
confidence: 99%